Using the FEM Method in the Prediction of Stress and Deformation in the Processing Zone of an Elastic/Visco-Plastic Material during Diamond Sliding Burnishing - Jarosław Chodór; Leon Kukiełka; Grzegorz Chomka; Łukasz Bohdal; Radosław Patyk; Marek Kowalik; Tomasz Trzepieciński; Andrii M. Radchenko (Applied Sciences, 2023)
This article concerns the application of the FEM method for the prediction of stress and deformation states in the workpiece during diamond sliding burnishing (DSB). An updated Lagrange (UL) description was used to describe the phenomena at a typical incremental step. The states of strain and strain rate are described by non-linear relationships without linearization. The material parameters were estimated during tensile tests to determine the characteristics of the 41Cr4 steel. Its hardness was also tested. Its aim was to prepare a table with the material properties of the above-mentioned steel and its implementation for numerical analyses. A Cowper–Symonds material model was used to model the displacement process of the wedge on an elastic/visco-plastic body reflecting the DSB process. The computer model was validated, and a good convergence of the results was obtained. Applications in the ANSYS/LS-Dyna program were developed to simulate the process of DSB. The results of numerical analyses were presented, among others, to explain the influence of the rake angle on the condition of the surface after machining, as well as the phenomenon of chip formation. The results of numerical simulations were verified experimentally on a test stand.